A Review on Lab Scale Cultivation of Calocybe Indica and Its Medicinal Value - Petchimuthu Priya; Petchimuthu Ramya; Ayyappan Athmarishi; Mariappan Vijaya; Palanipandi Revathy; Ramaiah Baladevi (International Journal of Nutrition, 2020)
Calocybe indica, a tropical edible mushroom and it is popular because it has good nutritive value and it can be cultivated commercially on a large scale. Mushrooms are in the great demand everywhere and hold a unique place in the world today due to their typical taste and rich in protein, vitamins, minerals. Other than nutritional value, it is also playing a major role in medicinal field. Milky mushroom is known to have anti-oxidant and anti-cancer effect. Paddy in particular used as a substrate in Milky mushroom considered as inexpensive and it is a popular variety among people because of its distinct flavor, higher protein content and shorter cropping duration compared to other cultivated mushrooms. The present study designed to explain how the mushroom was cultivated using paddy straw in India.
Keywords: Calocybe indica